The Mediating Effect of Reassurance-Seeking Behavior on the Influence of Viral Anxiety and Depression on COVID-19 Obsession Among Medical Students - Kim, Hyun Sub; Ahn, Junseok; Lee, Jukab; Hong, Youjin; Kim, Changnam; Park, Jangho; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Objectives Healthcare workers experienced great psychological burden due to the continuation of the COVID-19 pandemic. During the pandemic, medical healthcare workers experienced greater instances of insomnia, anxiety, depression, somatization, and obsessive-compulsive symptoms than the general population. This study aimed to explore the association between viral anxiety and obsession with COVID-19 among medical students with reassurance-seeking behavior as a mediator. Methods In October 2021, an online survey was conducted among medical students at the University of Ulsan College of Medicine. The clinical characteristics of 162 participants and their responses to rating scales, including stress and anxiety to viral Epidemics-6 items (SAVE-6), Coronavirus Reassurance-Seeking Behaviors Scale (CRBS), Patient Health Questionnaire-9 items (PHQ-9), and Obsession with COVID-19 scale were collected. Results Medical students’ obsession with COVID-19 was based on the PHQ-9 (β=0.15, p=0.01), SAVE-6 (β=0.43, p<0.001), and CRBS (β=0.38, p<0.001) scores (adjusted R2=0.49, F=39.9, p<0.001). Mediation analysis showed that medical students’ viral anxiety and depression directly influenced their obsession with COVID-19, and their reassurance-seeking behavior partially mediated the effects of depression or viral anxiety on obsession with COVID-19. Conclusions Medical students' viral anxiety and depression may affect their obsession with COVID-19, and reassurance-seeking behaviors may mediate this. Therefore, medical students should adopt adaptive coping strategies to prevent high levels of viral anxiety and recurrent reassurance-seeking behavior.